Study on role of rural health training centre (RHTC) as a supporting component to a primary health care system for NRHM programme in district Muzaffarnagar (UP) - Davey, Sanjeev; Raghav, Santosh Kumar; Muzammil, Khursheed; Singh, Jai Vir; Davey, Anuradha; Singh, Sujit Kumar; Garg, Gagan; Sehgal, Shruti (International Journal of Research in Medical Sciences, 2017)
Background:The role of RHTC set up under MCI requirement of medical colleges is rising in implementation of NRHM phase 2 programme (2012 onwards); as private medical colleges are expanding in India and they can be an important supporter in public-private partnership for national health programmes.Objective of current study was to assess the role of rural health training centre as a supporting component to a primary health care system for NRHM programme. Methods:The present study was carried out by comparative evaluation of the rural health and training centre of a private medical college with a sub-centre (Muzaffarnagar) on key RCH services of NRHM: a) Family planning materials distribution, b) ANC services and c) Immunization services. Inclusion criteria: Proper ethical approval from both primary health care system and private medical college authorities were obtained for the study. Study design: Prospective evaluation based study on ANM in SC & SN in RHTC in NRHM programme for 1 year duration from 1st January 2013 to 31st December 2013. Data analysis: The statistical data was analysed by Epi-info version 7.1.3. Results:The ANC services, family planning services and immunization services delivered under NRHM programme was found to statistically significantly contributed (P <0.05) by SN of RHTC as compared to ANM of SC in area of Bilaspur, Muzaffarnagar (Uttar Pradesh). Conclusion:RHTC of a private medical college in Muzaffarnagar (UP) is significantly contributing and supporting in RCH services of NRHM programme for primary health care system. RHTC of medical colleges can be an asset for public private partnership in NRHM programme.